(3bUjOI aj aVd GdYdes - (3eLghds
(3ChdgG (B:s
(3JYde jG aJi hGdLgd YGQ (B*** (3hdG jQVi HgG EdG MeGQ , Hg fdJ GdeYGdj aj GdMjGJj (B*** (3Hg YRj hLGgj cd YeQjs
(3BNQgG (B:s
(3GdfWb Rjf hGdSchJ SdGeI (B*** (3aEPG fWbJ adG Jcf HcKGQG , eG fOeJ Ydi SchJj eOI (B*** (3hdbO fOeJ Ydi GdcdGe eQGQGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs